(untitled) (Journal of Philosophy Culture and Political Science, 2016)
The article is devoted to the etymological explanation of the concepts of «tur” and “Turk”. In particular, do the georafic, linguistic, historical analysis of Persian, Chinese sources, highlighting the concept of “Turan”. Turan revealed georgafical word “tour”, which in the Middle Ages historically tied land Turkistan and Iran. And now frequent settlements similar to this concept. Thus the name of the tour, the Turkic lands under the influence of the Persian language, of course, does not remain outside of life parsoyazychnyh tribes of our region. Outlined changes “Turan” in “Turkestan”. However, the examples, and analyzed and the concept name “Tur”, “tura”, “Turba”, “Turban” “Turbat” “Turab” “Tula”.